The Effect of I-CARE Learning Model on the Students' Metacognition - Mamik Suendarti; Hawa Liberna (Universitas Sembilanbelas November Kolaka, 2018)
The general objective of this study was to find and analyze empirically the effect of the I Care learning model on the students' metacognition. The method used in this research was the experimental method. The affordable population in this study was grade X students of SMK Assyafiah which is located at Jalan Bukit Duri No.29, South Jakarta 2016/2017 academic year. The sample of the study was 60 students obtained through random sampling method that the researcher mixed in the population so that all subjects were considered the same. Data collection was done by documentation techniques (learning model variables) and test techniques (student metacognition variables). The collected data was then analyzed using the t-test. Before the data was analyzed, first descriptive statistical analysis and data requirements test (normality test, homogeneity test) were carried out. The results of the study showed that there was an influence of the I Care learning model on the students' metacognition. In other words, students' metacognition who used the I Care learning model was higher than the students' metacognition who used constructivism learning model.